Pengaruh Pelatihan dan Kompensasi Terhadap Produktivitas Kerja Karyawan Pada PT Bank Muamalat Indonesia KCU Medan Baru - Mutia Maudy Khasanah; Nurbaiti Nurbaiti (ITB AAS INDONESIA Surakarta, 2023)
This study aims to partially and simultaneously examine the effect of training and compensation on employee work productivity. The population in this study was 25 employees, and 25 employees were saturated. The data were processed using multiple linear regression analyses. The results of this study state that, first, training has a positive but insignificant effect on employee work productivity, partially with a t-count of 2.003 > t-table of 1.72 and a significant level of 0.058 > 0.05. Second, it states that partially compensating employees has a positive and significant effect on employee productivity with a t count of 2.003 > t table of 1.72 and a significant level of 0.001 0.05. Third, it states that training and compensation have a significant effect on employee productivity simultaneously, with an F-count of 8.776 and F-table of 3.44 meaning F-count > F-table. Result of significance = 0.002 0.05 Keywords: Training, Compensation, Work Productivity.